2016
DOI: 10.1111/gcbb.12381
|View full text |Cite
|
Sign up to set email alerts
|

Switchgrass growth and pine–switchgrass interactions in established intercropping systems

Abstract: Intercropping switchgrass (Panicum virgatum L.) with loblolly pine (Pinus taeda L.) has been proposed for producing bioenergy feedstock in the southeastern United States. This study investigated switchgrass growth and pine-switchgrass interactions at two established experimental fields (7-year-old Lenoir site and 5-year-old Carteret site) located on the coastal plain of eastern United States. Position effects (edge and center of switchgrass alley in intercropping plots) and treatment effects (intercropping vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
(128 reference statements)
0
12
0
1
Order By: Relevance
“…2d). The study site was initiated to investigate sustainability and productivity of loblolly pine and switchgrass intercropping to produce sawtimber and bioenergy feedstocks (Albaugh et al, 2012;Tian et al, 2015Tian et al, , 2017. Multiple experimental treatments including switchgrass and pine monocultures, and pine-switchgrass intercropping were established in a randomized complete block design (Albaugh et al, 2012).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…2d). The study site was initiated to investigate sustainability and productivity of loblolly pine and switchgrass intercropping to produce sawtimber and bioenergy feedstocks (Albaugh et al, 2012;Tian et al, 2015Tian et al, , 2017. Multiple experimental treatments including switchgrass and pine monocultures, and pine-switchgrass intercropping were established in a randomized complete block design (Albaugh et al, 2012).…”
Section: Study Sitementioning
confidence: 99%
“…The switchgrass received coated urea Arborite â fertilizer (65.6 kg N ha À1 , 6.6 kg P ha À1 , and 0.2 kg boron ha À1 ) during 2010, 2012, and 2014, but not during 2015 and 2016). Detailed descriptions of the study site, experimental design, and treatments can be found elsewhere (Albaugh et al, 2012(Albaugh et al, , 2014Tian et al, 2015Tian et al, , 2017.…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…A potential solution to offset this concern is to grow dedicated energy crops on marginal lands (Kang et al, 2013;Gelfand et al, 2013) or maximize land use by intercropping or alley cropping with other perennial crops (Blasier et al, 2012;Cacho et al, 2015;Tian et al, 2016). Intercropping is the growing of two or more crops of different species or varieties in close proximity to maximize the capture of photosynthetically active radiation and enhance the yield of both species compared with their growth in monoculture.…”
mentioning
confidence: 99%
“…Several studies have shown the benefits of intercropping woody species and switchgrass on yield and soil properties (Blasier et al, 2012;Gamble et al, 2014;Cacho et al, 2015;Muwamba et al, 2015;Tian et al, 2016). These benefits result from a diversification of outputs and a shortened time to reach economic production (Holzmueller and Jose, 2012;Susaeta et al, 2012).…”
mentioning
confidence: 99%